The Effect of Oven and Solar Portable Dryer Drying Methods In Terms Of the Antioxidant Activity of Moringa Oleifera Leaves: Pengaruh Metode Pengeringan Oven dan Solar Portable Dryer Ditinjau Dari Aktivitas Antioksidan Daun Kelor (Moringa oleifera) - Monang , Sihombing; Nugroho, Pulung; Yandistara, Mikrando Sheva (Science Technology and Management Journal, 2024)
Drying is a method that is widely used because this method is very simple and cheap. Drying techniques using conventional methods are the most widely used methods in drying food ingredients. Moringa leaves (Moringa oleifera) are a food ingredient widely used as a natural dye and contains many antioxidant components. Antioxidant components such as flavonoids, polyphenols, lycopene, and ß-carotene. In this research, the drying process was carried out by comparing two conventional drying methods by an oven and a portable solar dryer. The research method was carried out using a sample preparation process for the drying process of Moringa leaves, followed by an analysis of antioxidant activity using the DPPH method. From the results of research that has been carried out, antioxidant activity was found to be 5.22% in drying using the oven method and 14.02% in drying using the solar portable dryer method. The conclusion from the research that has been carried out is that the drying method will significantly influence the antioxidant activity of Moringa leaves. Apart from that, temperature conditions and the length of the drying process will also influence antioxidant activity.